2019
DOI: 10.1002/chem.201902422
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Catalytic Kinetic Resolution of α‐Branched Aldehydes through Formal Cycloaddition with Homophthalic Anhydrides

Abstract: A new catalytic methodology was developed to promote an efficient one‐pot kinetic resolution of racemic aldehydes with selectivity (s*) of up to 91 (99:1 d.r., >99 % ee) in a cycloaddition reaction with enolizable anhydrides to afford dihydroisocoumarin products (a core prevalent in natural products and molecules of medicinal interest) containing three contiguous stereocentres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Racemic primary alcohols [2-(naphthalen-1-yl)­propan-1-ol, 2-(naphthalen-2-yl)­propan-1-ol, 2-(4-isobutylphenyl)­propan-1-ol, and 2-(6-methoxynaphthalen-2-yl)­propan-1-ol], 2-(4-methoxyphenyl)-3-methylbutan-1-ol, and 2-methyl-4-phenylbutan-1-ol were prepared from the corresponding ketone by a known literature procedure via Wittig reaction followed by hydrolysis with an acid and reduction using NaBH 4 . The NMR data were found to be in accordance with the literature. , …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Racemic primary alcohols [2-(naphthalen-1-yl)­propan-1-ol, 2-(naphthalen-2-yl)­propan-1-ol, 2-(4-isobutylphenyl)­propan-1-ol, and 2-(6-methoxynaphthalen-2-yl)­propan-1-ol], 2-(4-methoxyphenyl)-3-methylbutan-1-ol, and 2-methyl-4-phenylbutan-1-ol were prepared from the corresponding ketone by a known literature procedure via Wittig reaction followed by hydrolysis with an acid and reduction using NaBH 4 . The NMR data were found to be in accordance with the literature. , …”
Section: Methodsmentioning
confidence: 99%
“…Its derivatives are also used as precursors for the total synthesis of natural products . Chiral 2-phenyl-1-propanol can be obtained by various methods (Scheme ). In 2017, Rychnovsky et al reported the kinetic resolution of 2-phenyl-1-propanol using homobenzotetramisole (HBTM) and resolution proceeded with a selectivity ( s ) of ≤6.2 (Scheme e) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Müller discovered that the homophthalic anhydride (HPA, 9 ) reacts smoothly with benzaldehyde in a basic medium at room temperature to form dihydroisocoumarin ( 10 ; Scheme 3 ) [ 14 , 15 , 16 ]. This strategy has been recently implemented for the kinetic resolution of racemic α-aryl-substituted branched aldehydes in the presence of a chiral squaramide-based bifunctional catalyst [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The diastereocontrol was equally high with aromatic aldehydes (80-94 ee%), albeit lower with aliphatic substrates, favoring the trans isomer in all cases. By developing related organocatalysts 2b, 3a and 3b, the Connon group expanded the scope of the Pinder reaction to encompass the kinetic resolution of chiral aldehydes, the selective formation of cis adducts with aldehydes, and the use of ketones as substrates, respectively [22][23][24][25]. These catalysts are suggested to operate initially by deprotonation of homophthalic anhydride by the basic nitrogen with the resulting ammonium species and the anhydride enolate being in turn held though hydrogen bonds by the Lewis acidic squaramide or urea module of the organocatalyst.…”
Section: Introductionmentioning
confidence: 99%